As relações entre educação e trabalho nas trajetórias de alunos de uma escola técnica : uma análise a partir de Bourdieu - Stefanini, Deborah Maria (2008)
The research aimed at analyzing the conditioning factors that motivate technical high school students to seek this kind of education and at understanding the meaning of this schooling to them as well as their expectations and future aspirations as regard to education and labor. The study, based on Pierre Bourdieu and collaborators sociological perspective, was developed based on the educational and professional trajectories analysis of students at a technical high school in São Paulo state. The analysis was preceded by a bibliographical study about the historical context of the professional education in Brazil, which had as a backdrop its main target public throughout the years, as well as the considerations concerning professionalization in the context of productive restructuring. The propensity to the technical education was analyzed based on the students social status and their internalized dispositions, designated habitus. It was observed that the inclination to the technical education is supported on a disposition that emphasizes the work instead of long studies. That trend establishes a contradiction lived by the families between the ideal the school longevity and the necessary the work. That internalized and durable disposition tends to determine the studies extension which, according to them, must be associated to the professional insertion. However, the education is assimilated as primordial for social mobility and the students internalize the idea that is necessary to continue studying. In this direction, the technical education, currently organized as a quickly course, is considered as a possibility for obtaining the studies extension, since other ways for that are uncertain or financially unfeasible. In most cases analyzed, the technical education has an instrumental meaning, as a way to aid in the self-subsistence for a future maintenance in the higher education, as a way to help to get better professions. On both cases, this education is assimilated as a form to enhance competition and not necessarily the obtention of work in the technical formation area.